Artificial Intelligence and Intellectual Property Protection in Indonesia and Japan - Rian Saputra; Tiara Tiolince; Iswantoro Iswantoro; Sanju Kumar Sigh (Lembaga Contrarius Indonesia, 2023)
This research aims to show the impact of artificial intelligence (AI) on fillings patent protection through patent rights. This research is normative legal research using a comparative legal approach in the Japanese AI protection system. The results indicate that the regulation of AI protection in intellectual property rights in Indonesia has not been accommodated in the Indonesian national legal system. However, the closest method for its protection can be performed through copyright, but it still has shortcomings, where AI in copyright protection is only considered the same as that of ordinary computer software in general, which should have significant differences. AI protection space in Japan can be accommodated through patents, provided that the AI in question contains elements or categories that can be protected through Japanese patents. AI protection as a patent right, in fact, has a very complicated and varied impact in Indonesia and Japan.